1995
DOI: 10.1002/psc.310010206
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of dinitrocarboxyphenylated melittin: The influence of C‐terminal chain shortening, N‐terminal substitution and prolin insertion at positions 5 and 10

Abstract: Peptides derived from the bee-venom melittin were fitted with the haptenic group dinitrocarboxyphenyl (Dncp) and tested in out-bred guinea pigs for immunogenicity by measuring the IgG anti-Dncp antibody response by ELISA. Dncp-conjugates comprising virtually the entire melittin proved to be strong immunogens producing antibody responses comparable to those of proteins. Weak responses were obtained with considerably shortened sequences. Conjugates with N-terminal Dncp gave markedly reduced antibody responses co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…A reference immunization was done with melittin (1± 26)K(Dncp)G, MD, previously synthesized and shown to give ELISA titres D r in guinea pigs of between 10 4 and 10 6 [13]. The data found for MD in the present experiment are shown together with those from the truncated peptide M(13±26)D in Figure. 1.…”
Section: Effect Of Chain Shortening At the N-terminus On Immunogenicitymentioning
confidence: 90%
See 4 more Smart Citations
“…A reference immunization was done with melittin (1± 26)K(Dncp)G, MD, previously synthesized and shown to give ELISA titres D r in guinea pigs of between 10 4 and 10 6 [13]. The data found for MD in the present experiment are shown together with those from the truncated peptide M(13±26)D in Figure. 1.…”
Section: Effect Of Chain Shortening At the N-terminus On Immunogenicitymentioning
confidence: 90%
“…It is evident and originally unexpected that the truncated peptide still elicits a considerable antibody response. The expectation was that in M(13±26)D a marked decrease in immunogenicity should become noticeable because previous data have shown that chain shortening at the C-terminus down to M(1±19)D did not remove guinea-pig immunogenicity [13] and that therefore a centrally …”
Section: Effect Of Chain Shortening At the N-terminus On Immunogenicitymentioning
confidence: 99%
See 3 more Smart Citations